2014
DOI: 10.1016/j.tet.2014.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium-catalyzed green oxidation of benzylic alcohols in water under air atmosphere

Abstract: Opportunely, we also found that VO(Hhpic)2 could also oxidize benzylamines to the corresponding imines with high selectivity using an ionic liquid solvent under an atmosphere of O2 (0.1 MPa), also with good recyclability (Scheme 2). 12(c)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 95 publications
3
18
0
Order By: Relevance
“…The catalytic oxidation of 1‐phenylethanol by the catalysts reported here compares well with the catalytic potential of molybdenum‐based catalysts [Mo VI O 2 (dha‐inh)(MeOH)] (where H 2 dha‐inh = Schiff base derived from dehydroacetic acid and isonicotinoyl hydrazide) and [Mo VI O 2 (bp‐bhz)(MeOH)] (H 2 bp‐bhz = benzoylpyrazolone and benzoyl hydrazide) reported recently where 78 and 84 % conversions, respectively, were obtained , . Notably, conversions with vanadium complexes [VO(Hhpic) 2 ] (where Hhpic = 3‐hydroxypicolinic acid) (51 %), [V 2 O 2 Mo 2 O 4 {µ‐(O 2 )}(4,4′‐ t Bubpy){µ‐(OMe) 2 }] (where 4,4′‐ t Bubpy = 4,4′‐di‐ tert ‐butyl‐2,2′‐bipyridyl) (63 %), and [V 2 O 2 W 2 O 4 {µ‐(O 2 )}(4,4′‐ t Bubpy){µ‐(OMe) 2 }] (28 %) are much lower than those achieved by the complexes reported here.…”
Section: Resultssupporting
confidence: 81%
“…The catalytic oxidation of 1‐phenylethanol by the catalysts reported here compares well with the catalytic potential of molybdenum‐based catalysts [Mo VI O 2 (dha‐inh)(MeOH)] (where H 2 dha‐inh = Schiff base derived from dehydroacetic acid and isonicotinoyl hydrazide) and [Mo VI O 2 (bp‐bhz)(MeOH)] (H 2 bp‐bhz = benzoylpyrazolone and benzoyl hydrazide) reported recently where 78 and 84 % conversions, respectively, were obtained , . Notably, conversions with vanadium complexes [VO(Hhpic) 2 ] (where Hhpic = 3‐hydroxypicolinic acid) (51 %), [V 2 O 2 Mo 2 O 4 {µ‐(O 2 )}(4,4′‐ t Bubpy){µ‐(OMe) 2 }] (where 4,4′‐ t Bubpy = 4,4′‐di‐ tert ‐butyl‐2,2′‐bipyridyl) (63 %), and [V 2 O 2 W 2 O 4 {µ‐(O 2 )}(4,4′‐ t Bubpy){µ‐(OMe) 2 }] (28 %) are much lower than those achieved by the complexes reported here.…”
Section: Resultssupporting
confidence: 81%
“…The performance of 2 as a catalyst for solvent free oxidation of the five alcohols included in our recent study compares quite favorably to several recently reported systems that function in the absence of added organic solvent . In many of the reported cases experiments appear to have been designed to maximize substrate conversion and several are impressive in this regard.…”
Section: Resultssupporting
confidence: 67%
“…Another paper describing the use of a simple zinc complex to catalyze the oxidation of benzyl alcohol to benzaldehyde with H 2 O 2 in water is limited in the same sense. [15] Other groups have described catalytic oxidations of alcohols in aqueous solution employing O 2 as the primary oxidant with water‐soluble oxovanadium and palladium(II) [17, 18] complexes. Further intriguing results have appeared in recent years that involve homogeneous catalytic alcohol oxidations occurring in the absence of any added solvent other than the water in which the oxidant itself is dissolved.…”
Section: Introductionmentioning
confidence: 99%
“…Ogawa and coworkers [20] recently reported the aerobic oxidation of benzylic alcohols in water, at 90 • C and 0.1 MPa O 2 , using 5 mol% of an oxovanadium(IV) complex of 4,4 / -di-tert-butyl bipyridine, 10, as the catalyst (Fig. 3).…”
Section: Tungsten and Vanadium Catalystsmentioning
confidence: 99%